THE LINGUISTICS OF VIRTUAL REALITY: THE SPEECH DYNAMICS OF EMOTION AND ABBREVIATIONS IN THE LANGUAGE OF SOCIAL NETWORKS (The Journal of Interdisciplinary Human Studies, 2026)
This article investigates the linguistics of virtual reality and the speechdynamics of emotions and abbreviations in the language of social networks. The resultsof the analysis illuminate the close interdependence between linguistic change and socialrelations, as well as the systematic impact that digital platforms exert on the culture ofcommunication.
Keywords: virtual reality, linguistics, social networks, emotion, abbreviations, speech dynamics, digital communication